Active surveillance of Hansen's Disease (leprosy): importance for case finding among extra-domiciliary contacts. - Maria L N Moura; Kathryn M Dupnik; Gabriel A A Sampaio; Priscilla F C Nóbrega; Ana K Jeronimo; Jose M do Nascimento-Filho; Roberta L Miranda Dantas; Jose W Queiroz; James D Barbosa; Gutemberg Dias; Selma M B Jeronimo; Marcia C F Souza; et al. (Public Library of Science (PLoS), 2013)
Hansen's disease (leprosy) remains an important health problem in Brazil, where 34,894 new cases were diagnosed in 2010, corresponding to 15.3% of the world's new cases detected in that year. The purpose of this study was to use home visits as a tool for surveillance of Hansen's disease in a hyperendemic area in Brazil. A total of 258 residences were visited with 719 individuals examined. Of these, 82 individuals had had a previous history of Hansen's disease, 209 were their household contacts and 428 lived in neighboring residences. Fifteen new Hansen's disease cases were confirmed, yielding a detection rate of 2.0% of people examined. There was no difference in the detection rate between household and neighbor contacts (p = 0.615). The two groups had the same background in relation to education (p = 0.510), household income (p = 0.582), and the number of people living in the residence (p = 0.188). Spatial analysis showed clustering of newly diagnosed cases and association with residential coordinates of previously diagnosed multibacillary cases. Active case finding is an important tool for Hansen's disease control in hyperendemic areas, enabling earlier diagnosis, treatment, decrease in disability from Hansen's disease and potentially less spread of Mycobacterium leprae.